The Cerebellum and Its Wrapping Meninge: Developmental Interplay between Two Major Structures - Catala, Martin (Neuropediatrics, 2017)
Meninges have long been considered as a protective and supportive tissue for the central nervous system. Nevertheless, new developmental roles are now attributed to them. The meninges that surround the cerebellum come from the cephalic mesoderm. They are essential for the cerebellum to develop normally. They induce and maintain the basal lamina and glia limitans. In the absence of these structures, the external granular cells of the cerebellum migrate aberrantly and penetrate the subarachnoid space. The molecules involved in the recognition between the cerebellar primordium and the basal lamina belong to two groups in humans: dystroglycan and laminin on the one hand, and GPR56 and collagen III on the other. Finally, molecules secreted by the meninges and acting on the cerebellum begin to be demonstrated; such is the case of SDF1 secreted under the action of FOXC1.
Keywords: developmental biology; cell interaction; genes; cerebellar polymicrogyria